The middle voice in Baltic - Holvoet, Axel (Valency, argument realization and grammatical relations in Baltic ;, 2020)
"Presentis a collection of studies on middle-voice grams in Baltic, that is, on a widely ramified family of constructions with different syntactic and semantic properties but sharing a morphological marker of reflexive origin. Though the emphasis is on Baltic, ample attention is given to other languages as well, especially to Slavonic. The book offers many new insights into questions of syntactic and semantic interpretation, correct demarcation and diachronic explanation of middle-voice grams. The relationship between reflexive and middle, the workings of metonymy, changes in syntactic structure and lexical input as factors determining diachronic shifts within the middle-voice domain and transitions from one middle-voice gram to another - these are among the topics discussed in the book, which, beyond its relevance to Baltic and Slavonic scholarship, is also a contribution to the typology of the middle voice"--